Pengaruh Informasi Biaya Relevan dan Pengendalian Internal terhadap Pengambilan Keputusan Manajemen Pada Perusahaan Manufaktur sebagai Kajian Literatur - Hernawan, Danar; Nausta Pardede, Tiolina Evi (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to examine the influence of relevant cost information and internal control on managerial decision-making in manufacturing companies through a literature review approach. This research employs the Systematic Literature Review (SLR) method to systematically identify, evaluate, and synthesize previous studies related to the research topic. The data sources were obtained from national and international scientific journal articles published between 2015 and 2025 and accessed through several academic databases such as Google Scholar and Garuda. The analysis process was conducted by selecting articles based on topic relevance, publication quality, and their relation to the research variables. The results of the literature review indicate that relevant cost information plays an important role in assisting management in evaluating various decision alternatives more rationally and efficiently. In addition, effective internal control systems help ensure the reliability of accounting information and minimize the risk of errors in the decision-making process. Therefore, the integration of relevant cost information and effective internal control systems can improve the quality of managerial decision-making in manufacturing companies